Intensification of pretreatment and pressure leaching of copper anode slime by microwave radiation - Yang, Hong-ying; Ma, Zhi-yuan; Huang, Song-tao; Lv, Yang; Xiong, Liu (Journal of Central South University, 2015)
The application of microwave irradiation for pretreatment of copper anode slime with high nickel content prior to pressure sulfuric acid leaching has been proposed. The microwave-assisted pretreatment is a rapid and efficient process. Through the technology of microwave assisted pretreatment-pressure leaching of copper anode slime, copper, tellurium, selenium and nickel are almost completely recovered. Under optimal conditions, the leaching efficiencies of copper, tellurium, selenium and nickel are 97.12%, 95.97%, 95.37% and 93.90%, respectively. The effect of microwave radiation on the temperature of copper anode slime and leaching solution is investigated. It is suggested that the enhancement on the recoveries of copper, tellurium and selenium can be attributed to the temperature gradient which is caused by shallow microwave penetration depth and super heating occurring at the solid-liquid interface. The kinetic study shows that the pressure leaching of copper anode slime, with and without microwave assisted pretreatment, are both controlled by chemical reactions on the surfaces of particles. It is found that the activation energy calculated for microwave-assisted pretreatment-pressure leaching (49.47 kJ/mol) is lower than that for pressure leaching which is without microwave assisted pretreatment (60.57 kJ/mol).